2017
DOI: 10.1136/bcr-2016-217372
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated limbal epithelial transplantation and penetrating keratoplasty postchemical injury: a 14-year follow-up

Abstract: An 11-year-old girl presented to our tertiary eye care centre with a 9-month-old history of lime injury in the left eye in 1999 with vision of counting fingers close to the face. She initially underwent superficial keratectomy with amniotic membrane graft in 1999. Subsequently, cultivated limbal epithelial transplantation was performed in 2001 which improved her vision to 20/400. Following development of pannus and symblepharon in the left eye, she underwent pannus resection and conjunctival limbal autograft i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…No epithelial issues were noted in our case of total LSCD demonstrating the efficacy of these smaller grafts. A few studies have reported inadequate epithelial stability with grafts involving <90 o of limbus while others have demonstrated good epithelialization with two clock-hour grafts [8] , [9] , [10] , [11] . Another added advantage of mini-CLAU is that the procedure may be attempted even in cases with partial LSCD in the donor eye, provided the residual limbus is at least 6 clock-hours.…”
Section: Discussionmentioning
confidence: 99%
“…No epithelial issues were noted in our case of total LSCD demonstrating the efficacy of these smaller grafts. A few studies have reported inadequate epithelial stability with grafts involving <90 o of limbus while others have demonstrated good epithelialization with two clock-hour grafts [8] , [9] , [10] , [11] . Another added advantage of mini-CLAU is that the procedure may be attempted even in cases with partial LSCD in the donor eye, provided the residual limbus is at least 6 clock-hours.…”
Section: Discussionmentioning
confidence: 99%
“…For a review of the specific complications of these procedures see Yin et al [64]. Penetrating keratoplasty (PKP) is frequently undertaken as a second procedure following LSC transplantation in order to replace deep scarred stroma, with the ultimate aim of restoring sight [65][66][67].…”
Section: Tissue Transplant Techniques: Conjunctival-limbal and Keratomentioning
confidence: 99%
“…This may be due to hypoxia, mechanical injury, or limbal stem cell deficiency [19,20]. Corneal transplantation, the most common solid tissue transplantation procedure, can cause corneal NV and subsequent LK via suture-induced inflammation and alloimmune responses [21,22]. Corneal NV can reduce graft survival after corneal transplant [23].…”
Section: Etiologymentioning
confidence: 99%